2000
DOI: 10.1101/gr.10.8.1204
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Protein Function by Genomic Context: Quantitative Evaluation and Qualitative Inferences

Abstract: Various new methods have been proposed to predict functional interactions between proteins based on the genomic context of their genes. The types of genomic context that they use are Type I: the fusion of genes; Type II: the conservation of gene-order or co-occurrence of genes in potential operons; and Type III: the co-occurrence of genes across genomes (phylogenetic profiles). Here we compare these types for their coverage, their correlations with various types of functional interaction, and their overlap wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
325
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 469 publications
(338 citation statements)
references
References 35 publications
9
325
0
4
Order By: Relevance
“…[23] or genomic context data [17]. Here we combine 3D structure data with both genomic context data and functional genomics data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] or genomic context data [17]. Here we combine 3D structure data with both genomic context data and functional genomics data.…”
Section: Discussionmentioning
confidence: 99%
“…For bolA, we have analyzed a number of socalled ''genomic context'' [17] types (gene fusion, gene-order conservation, and the co-occurrence of genes among sequenced genomes) using the genomic context server STRING [18]. Two types of genomic context indicate an interaction between BolA and a mono-thiol glutaredoxin/PICOT-homology domain [8]: Their conserved occurrence as neighbors in Bacterial genomes (Fig.…”
Section: Gene Order Conservation and Gene Co-occurrence Indicate An Imentioning
confidence: 99%
“…To discover functional associations between genes on the basis of the genomic context of orthologs of C. elegans genes, we used the phylogenetic profile method Huynen et al 2000;Wolf et al 2001) and the gene neighbors method (Dandekar et al 1998;Overbeek et al 1999;Bowers et al 2004). For both methods, we analyzed 424 bacterial genome sequences (31 archeaebacteria and 393 eubacteria, downloaded from NCBI in December 2006).…”
Section: Inferring Functional Associations From Phylogenetic Profilesmentioning
confidence: 99%
“…Their hypothesis is based on the observation that individual genes in one organism that are fused in another organism into a single chain, the Rosetta sequence, probably have a functional relationship and may interact physically with each other. Huynen et al (2000) performed a statistical analysis on Mycoplasma genitalium to study the significance of functional links identified among genes through the Rosetta method. They concluded that the identification of genes in one organism that match a fused gene in a second organism provide an 80% statistically significant evidence of a similar function of the gene pairs, a presence in a protein complex by 70%, and a physical interaction by 60%.…”
Section: Network/pathway Construction and Analysismentioning
confidence: 99%